CULTURAL AND ENVIRONMENTAL INFLUENCES ONPARENTING HIGHLY SENSITIVE CHILDREN - Shimron, Bar (E-Journal VFU, 2025)
Cultural and Environmental Influences on Parenting Highly Sensitive Children The parenting of highly sensitive children (HSCs) is profoundly affected by cultural and environmental influences, shaping both their emotional experiences and developmental outcomes. Highly sensitive children, estimated to represent 15% to 20% of the population, process sensory information more intensely, making them particularly vulnerable to their surroundings (Mak & Zhang, 2021, Learning Mole, n.d.). Understanding how different cultural norms dictate parenting styles and emotional regulation strategies is essential, as these factors can significantly impact how HSCs navigate their emotional landscapes (Johnson & Smith, 2021, Moller, 2020). Cultural contexts play a pivotal role in defining emotional expression and parenting approaches. For instance, individualistic cultures, such as the United States, often emphasize self-expression and cognitive strategies for managing emotions, while collectivist cultures, like those found in East Asia, prioritize emotional suppression and social harmony (Child Research Net, 2019, Wang & Liu, 2021). These differences can complicate how parents perceive and respond to the unique emotional needs of HSCs, leading to diverse parenting strategies that can either support or hinder a child’s development (Moller, 2020). Furthermore, societal expectations may place additional stress on parents, especially in varying economic conditions, affecting their ability to provide nurturing environments conducive to emotional growth (Neurodivergent Insights, n.d.). Environmental influences also significantly shape parenting dynamics, particularly through factors such as parenting stress and family routines. High levels of stress, often exacerbated by crises like the COVID-19 pandemic, can detrimentally impact the quality of parent-child relationships, resulting in heightened internalizing behaviors among sensitive children (Danhoff & Vance, 2023, Connected Families, n.d.). Establishing a supportive home environment—characterized by validation, calm spaces, and structured routines—has been shown to enhance emotional resilience in HSCs, promoting their overall well-being (Schoenfeld, 2021, Moller, 2023). Despite the growing recognition of the unique challenges faced by parents of highly sensitive children, misconceptions and critiques persist regarding the classification and implications of high sensitivity. While some advocate for a deeper understanding of HSC traits, others argue for a more nuanced view that acknowledges the complexities of neurodiversity, including autism spectrum conditions (Moller, 2023, Equitable Growth, 2021). Overall, effective parenting of HSCs requires a combination of cultural sensitivity, emotional attunement, and environmental awareness to foster resilience and adaptability in an increasingly complex world.